2012
DOI: 10.1186/2049-1891-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and glutamate supplementation raise milk glutamine concentrations in lactating gilts

Abstract: Glutamine is the most abundant amino acid in milk, and lactation is associated with increased glutamine utilization both for milk synthesis and as a fuel for the enlarged small intestine. A number of recent studies have indicated that lactation is accompanied by a mild catabolic state in which skeletal muscle proteins are degraded to provide amino acids that are used to synthesize additional glutamine. In this study we tested the hypothesis that supplemental L-glutamine or the commercially available glutamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 25 publications
3
36
0
2
Order By: Relevance
“…Although glutamine and glutamate are usually regarded as nonessential amino acids there is increasing evidence that they should be considered as conditionally essential in a number of physiological and pathological states. We, and others, have shown that lactation represents a mild catabolic state due, in part, for the need to provide additional glutamine for milk synthesis and as a fuel for the enlarged intestine, and results in a loss of endogenous protein (lean body mass) in the sow (Clowes et al, 1998(Clowes et al, , 2005Kim and Easter, 2001;Manso et al, 2012). Studies with recently weaned piglets have shown benefits of supplemental glutamine (Kitt et al, 2002;Lopez-Pedrosa, et al, 2007;Wang et al, 2008;Wu et al, 1996;Xiao et al, 2012a,b,c;Yoo et al, 1997;Yi et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although glutamine and glutamate are usually regarded as nonessential amino acids there is increasing evidence that they should be considered as conditionally essential in a number of physiological and pathological states. We, and others, have shown that lactation represents a mild catabolic state due, in part, for the need to provide additional glutamine for milk synthesis and as a fuel for the enlarged intestine, and results in a loss of endogenous protein (lean body mass) in the sow (Clowes et al, 1998(Clowes et al, , 2005Kim and Easter, 2001;Manso et al, 2012). Studies with recently weaned piglets have shown benefits of supplemental glutamine (Kitt et al, 2002;Lopez-Pedrosa, et al, 2007;Wang et al, 2008;Wu et al, 1996;Xiao et al, 2012a,b,c;Yoo et al, 1997;Yi et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…The experiment was carried out from September to October 2010. One week prior to the expected date of delivery sows were transferred to individual farrowing crates and body weight (estimated using a biometric method based on thoracic circumference and body length, Manso et al, 2012) was 298 712 and 293 711 Kg, and back fat thickness (ultrasound) was 20.770.6 and 13.0 70.2 mm (p o0.05), for Control and Aminogut sows respectively. The temperature in the farrowing house ranged between 22 and 34 1C with a mean relative humidity between 43% and 97%.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…240, Art. 1582, Setembro, 2013 gestação e lactação (WATFORD, 2008;ROTH, 2008;WU, 2010;MANSO, et al 2012 Diversos trabalhos foram executados com diversos tipos celulares, como linfócitos, macrófagos, enterócitos, entre outros, com a finalidade de se testar a utilização da glutamina pelas células, mostrando que a manutenção das estruturas e funções das células, bem como o aumento da proliferação celular, puderam ser obtidos com a utilização da glutamina em meios de cultura (CALDER & YAQOOB, 1999;NEWSHOLME, 2001;LI et al 2007;JIANG et al 2009). …”
Section: Com Base Nestas Novas Classificações Dos Aminoácidos O Uniteunclassified
“…240, Art. 1582, Setembro, 2013 O aumento da concentração de glutamina e de glutamato no leite de porcas foi verificada por MANSO (2012) Segundo YOO et al (1997) quando leitões estão expostos a infecção moderada, a suplementação de glutamina mantém normal a concentração da glutamina muscular intracelular, as populações leucocitárias e as funções dos linfócitos. O fortalecimento da imunidade do leitão associado com a aceleração do desenvolvimento das vilosidades intestinais e proliferação dos enterócitos promovem em conjunto a diminuição da mortalidade de leitões pós-desmame, além disso, o efeito catabólico causado pela situação de estresse ou por doenças é diminuído, conferindo a importância da utilização da glutamina nas fases de gestação, lactação e pós-desmame.…”
Section: Melhoria Da Qualidade Do Leiteunclassified